Motor assessment instruments and psychometric procedures: A systematic review - Pâmella de Medeiros; Marcela Almeida Zequinão; Fernanda Cerveira Fronza; João Otacilio Libardoni dos Santos; Fernando Luiz Cardoso (Desafio Singular, 2017)
It was our objective to identify the psychometric elements to an epistemological reflection through a systematic review of cross-cultural validation procedures of TGMD-2 batteries, MABC-2 and KTK. Searches were carried out by two evaluators independently without year and language restrictions in six databases: Web of Science, Science Direct, Lilacs, Scopus, Pubmed and The ScientificElectronic Library Online - SciELO. The key words used were: "MABC", "TGMD" and "KTK" all of them combined with the word "validity". There was a total of 734 articles, of which, after the exclusion criteria, remained only 11 studies. It was found that there are differences between the authors in relation to the psychometric factors taken into account in cross-cultural validation. So that there was a lack of unanimity of the validation criteria of all studies in this field.